Acetylation of Î³-mangostin Isolated from the Mangosteen Pericarp (Garcinia mangostana Linn.) and Their Antidiabetic Activity - Rafsanjani, Ega Rocky Maulana; Fadlan, Arif; Ersam, Taslim (IPTEK Journal of Proceedings Series, 2020)
Mangosteen (Garcinia mangostana Linn) is one of the most well-known plants in Indonesia. Mangosteen contains many derivatives of oxygenated and prenylated xanthones from phenolics which exhibit diverse biological activities such as antioxidants, antimalarials, anti-allergies, anti-tumors, antiviral, antibacterial, anti-inflammatory, anti-fungal, anticancer, and antidiabetic. Modification of xanthone compounds is known to increase antidiabetic activity and it is known that Î±- and Î²-mangostin acetylated can be produced from the modification of Î±- and Î²-mangostin using acetic anhydride. In this study, as many as 1.43 grams (1.59%) of the Î³-mangostin compound were successfully isolated from the ethyl acetate extract of mangosteen pericarp. Modification of Î³-mangostin through the acetylation reaction produces acetylated Î³-mangostin in the form of 3,6,7-tri-methylester-Î³-mangostin as much as 32.9 mg (63%). Antidiabetic test results showed Î³-mangostin had an IC50 value of 8.55 Î¼M, while the IC50 value of 3.6.7-tri-methylester-Î³-mangostin was 1.82 Î¼M. Acarbose as a positive control has an IC50 value of 4.48 Î¼M. This shows that modification can increase antidiabetic activity.